The eyes of the people democracy in an age of spectatorship - Green, Jeffrey E. (Jeffrey Edward) (New York ; Oxford : Oxford University Press, 2010)
For centuries it has been assumed that democracy must refer to the empowerment of the People's voice. In this book, Green argues that it is both possible and desirable to understand democracy in terms of what the People gets to see instead of the traditional focus on what it gets to say.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Representative government and representation; Collective behavior -- Political aspects; Democracy; Plebiscite; Political participation